Simulation Design Bandpass Filter Microstrip Center Frequency 113 Mhz Using Hairpin Structure - Banjarnahor, Jonathan Japalti; Wildan, Muh.; Zulkarnain, Aringga (Indonesian Journal of Education and Mathematical Science, 2024)
Bandpass filter is an important component in aviation equipment that functions to pass the desired frequency and to stop unwanted frequencies. In this research, the simulation design was carried out with a bandpass filter microstrip which works on the center frequency 113 MHz using hairpin structure for the receiver navigation analyzer system. This system is one of the systems installed in drone in implementation ground inspection for ILS/VOR equipment. Bandpass filter is designed using a simulation software with various dielectric materials / substrates, such as R04350, FR-4, and RT5880, for comparison purposes. The simulated parameter values obtained include return loss, insertion loss, and bandwidth.